2015
DOI: 10.1177/1940161215613060
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Intergovernmental Organizations in the “Battle over Framing”

Abstract: Current studies focusing on the media’s coverage of international conflicts have largely overlooked the important role that intergovernmental bodies may play in their framing. Still missing is an examination of how and to what degree do actions performed by such bodies help define the way journalists report on ongoing conflicts. We claim that in the absence of credible state actors to rely on for information during conflict, journalists will turn to statements made by international bodies as alternative source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…A recent meta-analysis of public diplomacy research demonstrated the increasing prominence of public diplomacy research across various research fields, with communication studies making up the highest number of public diplomacy studies since 1965 (Sevin et al 2019). Research in this field has mainly focused on analyzing how countries and their related entities are portrayed in newspapers or represent themselves over long periods (Metzgar and Su 2017;Golan and Lukito 2017;Rettig and Avraham 2016;Zhang et al 2016), during political (O'Boyle 2019) or sporting (Zhou et al 2013) events, or in times of conflict or crisis (Jungblut 2017;Sheafer et al 2014) in order to come to conclusions about agenda-building effects and implications for the perceived country image. However, only a few scholars have actually investigated the public and their reactions to public diplomacy communication efforts, or the relationships between public diplomacy actors and their publics, to show evidence of their interactions, for instance, on social media (Park and Lim 2014;Samuel-Azran et al 2019;Zhong and Lu 2013) and the construction of a country's image (e.g., through Google Search, see Ingenhoff et al 2020).…”
Section: Commonly Used Research Designs In Public Diplomacy Researchmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent meta-analysis of public diplomacy research demonstrated the increasing prominence of public diplomacy research across various research fields, with communication studies making up the highest number of public diplomacy studies since 1965 (Sevin et al 2019). Research in this field has mainly focused on analyzing how countries and their related entities are portrayed in newspapers or represent themselves over long periods (Metzgar and Su 2017;Golan and Lukito 2017;Rettig and Avraham 2016;Zhang et al 2016), during political (O'Boyle 2019) or sporting (Zhou et al 2013) events, or in times of conflict or crisis (Jungblut 2017;Sheafer et al 2014) in order to come to conclusions about agenda-building effects and implications for the perceived country image. However, only a few scholars have actually investigated the public and their reactions to public diplomacy communication efforts, or the relationships between public diplomacy actors and their publics, to show evidence of their interactions, for instance, on social media (Park and Lim 2014;Samuel-Azran et al 2019;Zhong and Lu 2013) and the construction of a country's image (e.g., through Google Search, see Ingenhoff et al 2020).…”
Section: Commonly Used Research Designs In Public Diplomacy Researchmentioning
confidence: 99%
“…Public diplomacy research uses different research designs, including quantitative content analysis (e.g., Collins et al 2019;Lee 2007;Zhang et al 2018) and qualitative analysis (e.g., Avraham 2014) or, occasionally, a mixture of the two (Golan 2013;Rettig and Avraham 2016;White and Radic 2014). Although an increasing amount of potential research data, particularly social media content, has been examined using automated content analysis, to date, this method has only played a minor role in public diplomacy research (Huang and Wang 2019;Sheafer et al 2014).…”
Section: Commonly Used Research Designs In Public Diplomacy Researchmentioning
confidence: 99%
See 3 more Smart Citations